Manufacturing process selection handbook - Swift, K. G. (Butterworth-Heinemann, 2013)
The selection of suitable manufacturing processes is an essential part of the design process but it is often secondary to the choice of component form and shape, regularly resulting in late engineering changes, high costs and compromised quality. Novice design engineers in particular lack the wide experience of different manufacturing processes such as casting, forming, machining, fabrication and joining of materials needed to make an informed, appropriate and cost-effective manufacturing choice from the breadth of possibilities for a particular design. Building on content from the authors' earlier introductory Process Selection, 2e guide, this expanded handbook fills the knowledge gap with concise descriptions of many different processes.
Keywords: Manufacturing processes -- Planning.; Engineering design.; elektronické knihy; electronic books